The Architecture of Langgar Dhuwur in Java: Vernacular Forms in Religious Architecture - Arif Budi Sholihah; Asrul Mahjuddin Ressang; Wisnu Setiawan (Journal of Islamic Architecture, 2024)
Research on Friday Mosques dominates the study of religious buildings in Java. Meanwhile, research on small mosques, particularly Langgar Dhuwur, remains limited. The purpose of this study is to examine two Langgar Dhuwur in Kauman Yogyakarta from architectural and narrative perspectives in order to reveal the architectural characteristics as well as their role in society. Direct visual observations, measured drawings, and narratives about the study’s context were conducted. Five major themes from the observations were analyzed and discussed to draw significant conclusions. It is concluded that Langgar Dhuwur is a unique architectural type that preserves Indonesia’s vernacular and pre-Islamic architecture. Langgar Dhuwur in Kauman designated the second floor as a sacred area following the Hindu-Buddhist concept of Triloka (Svarloka). As a public building, Langgar Dhuwur serves as a place of worship as well as a cultural and social center. Therefore, it can be regarded as one of Indonesia’s religious architectural treasures due to its distinctive architectural style and rich history. It is recommended that the existence of Langgar Dhuwur, which has a multifunction role in community development, be preserved. Future design needs to emphasize an architectural typology that follows residential architecture, flexible space, and an open plan to accommodate various activities in the micro-scale community area.